Indices of Lipid Metabolism in Blood Serum in Animals with Some Non-Contagious Diseases and After Cooling - Zemlianskyi, Andrii O. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 174